Antisense Silencing of the creA Gene in Aspergillus nidulans - Bautista, L. Fernando (American Society for Microbiology, 2000)
Antisense expression of a portion of the gene encoding the major carbon catabolite repressor CREA in Aspergillus nidulans resulted in a substantial increase in the levels of glucose-repressible enzymes, both endogenous and heterologous, in the presence of glucose. The derepression effect was approximately one-half of that achieved in a null creA mutant. Unlike results for that mutant, however, growth parameters and colony morphology in the antisense transformants were not affected.